Preface - Hackwitz, Kim von (2015)
Ancient Death Ways has been an annual workshop at the Department of Archaeology and Ancient History, Uppsala University, Sweden, since 2012. It is part of the Stone Age Seminar in Uppsala arranged by the Department in collaboration with the Societas Archaeologica Upsaliensis (SAU). The aim of the workshop is to bring together researchers currently working with mortuary practices and/or human remains from prehistoric archaeological sites and to work in an interdisciplinary environment, by opening the debate to all scholars and disciplines somehow involved in these subjects. This format emphasises the interaction and exchange of ideas as well as an updated debate on theory, methods and ethics, within a vibrant network.